2006
DOI: 10.1093/eurheartj/ehl041
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular outflow tract obstruction and sudden death risk in patients with hypertrophic cardiomyopathy

Abstract: LVOTO is associated with an increased risk of SD/ICD that is related to the severity of obstruction and the presence of other recognized risk factors for SD. The low sudden death mortality in asymptomatic patients with LVOTO and no other SD risk markers suggests that aggressive interventions to reduce LVOTO are unwarranted in this group. Further studies are required to determine the most appropriate treatment strategies (ICD or gradient reduction) in patients with additional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
253
1
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(270 citation statements)
references
References 39 publications
4
253
1
12
Order By: Relevance
“…Association was demonstrated between the severity of obstruction and predisposition to sudden death, which was also related to the presence of other risk factors 35 . However, the dynamic character of the obstruction makes the detection of independent risk predictor difficult, in addition to the fact that its isolated presence does not stand and indication for implantation of automatic defibrillator 2 .…”
Section: Clinical Picturementioning
confidence: 86%
“…Association was demonstrated between the severity of obstruction and predisposition to sudden death, which was also related to the presence of other risk factors 35 . However, the dynamic character of the obstruction makes the detection of independent risk predictor difficult, in addition to the fact that its isolated presence does not stand and indication for implantation of automatic defibrillator 2 .…”
Section: Clinical Picturementioning
confidence: 86%
“…Dlatego też znaczenie badań obrazowych ograniczano do określenia obecności ekstremalnego przerostu LV. Jednocześnie coraz częściej pojawiały się doniesienia o dodatkowych wskaźnikach prognostycznych, takich jak powiększenie wymiaru LA, zawężanie w LVOT [37,39], obecność koniuszkowego tętniaka LV czy wreszcie postać HCM z dysfunkcją skurczową i z postępującą dylatacją LV (end-stage HCM) [13,24,30,163]. Największe nadzieje wzbudziły jednak prace wskazujące na obecność ogniskowego zwłóknienia w przerośniętym mięśniu sercowym jako nowego czynnika rokowniczego, na podstawie LGE metodą CMR.…”
Section: Rola Metod Obrazowych W Identyfikowaniuunclassified
“…Ocena morfologii przerostu oraz masy lewej komory w badaniu trójwymiarowym wielopłaszczyznowym; dominuje przerost ściany bocznej i dolnej (strzałki) Rycina 9. Prezentacja trójwymiarowa; przekroje poprzeczne od poziomu pierścienia trójdzielnego po wierzchołek prawej komory; duży przerost wolnej ściany prawej komory w stratyfikacji ryzyka SCD [37][38][39]. Dlatego też u każdego chorego należy zmierzyć PPG w LVOT w spoczynku, w półleżącej pozycji oraz przy gradiencie < 50 mm Hg również po prowokacji próbą Valsalvy i pionizacją [40][41][42].…”
unclassified
“…38 A recent study from the same group showed that left ventricular outflow tract obstruction in asymptomatic patients with no other SD risk markers was not related to increased mortality and did not warrant aggressive interventions. 39 Prophylactic pharmacological therapy with β-blockers or calcium channel antagonists has frequently been used, but efficacy in SD prevention has not been established. Empiric use of amiodarone has been reported to be associated with improved survival in one observational study with historical controls.…”
Section: 27mentioning
confidence: 99%